Pengaruh Kompetensi Kewirausahaan dan Inovasi Produk terhadap Keberhasilan Usaha dengan Efikasi Diri sebagai Variabel Moderasi pada Usaha Mikro Kecil di Kota Jambi - Taufiqoh; Idham Khalik; Besse Wediawati (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the influence of business competence and product innovation on business success with self-efficacy as a moderating variable. The research method uses a quantitative descriptive approach with a Likert-scale questionnaire survey and literature review. The population includes Micro and Small Enterprises in Jambi City, totaling 46,996 MSMEs in 2024, with a sample of 175 Micro and Small Business actors. Data analysis was conducted using SmartPLS to test the validity, reliability, and influence between variables. Entrepreneurial competence has a positive but not significant effect on business success. Product innovation has a positive and significant effect on business success. Self-efficacy was not proven to moderate the relationship between entrepreneurial competence and business success. Self-efficacy was also not proven to moderate the relationship between product innovation and business success. Research results show that the success of MSME businesses in Jambi City is more influenced by the business actors' ability to innovate products, while entrepreneurial competence and self-efficacy have not yet become dominant factors in increasing business success.